2012
DOI: 10.4028/www.scientific.net/amm.155-156.42
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation on the Effect of the Position of the Nozzle in End Milling under Minimum Quantity Lubrication Condition

Abstract: Stricter environmental regulations are making the use of an ample amount of conventional coolant impossible because of its negative impact on the environment. Consequently, the use of minimum quantity lubrication (MQL) has been regarded as an promising alternative to conventional fluid coolant applications. Despite several studies, there have been a few investigations about the influence of the MQL nozzle position, such as distance from tool-workpiece contact zone, elevation angles, the included angle between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Consequently, the application of MQL technique is considered as an outstanding alternative compared to normal cutting fluid application. The effect of MQL parameters on machining is the most saliency such as nozzle elevation angle, distance from the nozzle tip to the machined surface, lubricant flow rate and air pressure [13][14][15]. Also, MQL parameters also have different technological parameters such as nano-particle, vegetable oil, cryogenic, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the application of MQL technique is considered as an outstanding alternative compared to normal cutting fluid application. The effect of MQL parameters on machining is the most saliency such as nozzle elevation angle, distance from the nozzle tip to the machined surface, lubricant flow rate and air pressure [13][14][15]. Also, MQL parameters also have different technological parameters such as nano-particle, vegetable oil, cryogenic, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…They found that spraying the cutting fluid at the exit point (disengagement point) resulted in the longest tool life due to elimination of chip adhesion. Yuan et al 8 evaluated the effect of the nozzle position in an end milling process of 50CrMnMo, a structured alloy steel. The position of 60° away from the disengagement point led to prolonged tool life.…”
Section: Introductionmentioning
confidence: 99%
“…Although for the cutting process it is beneficial to use cutting fluids, from the ecological and economical point of view [1,2,3], efforts are being made to reduce and even eliminate the use of cutting fluids, thus leading to dry cutting.…”
Section: Introductionmentioning
confidence: 99%